Dengan Adanya Digital Pengadaan dan Inovasi Rantai Pasok dalam suatu organisasi, Apakah dapat meningkatkan kinerja bisnis yang berkelanjutan ? - Ruth Noviyanti; Kurniawati Kurniawati; Yolanda Masnita (JURNAL ILMIAH EDUNOMIKA, 2024)
Procurement has experienced changes functionally and role, which previously as a transactional and administrative, currently to experience development in a strategic within the organization by the use of technology. Not all organizations can maximize the use of digitalization due to factor of the cost and human resource factor. The unpreparedness of these factors can affect the results obtained in the performance of the supply chain and organizational performance. This research is based on the theory of resource Based View (RBV),to produce sustainable organization and competitive advantage within the organization, can be achieved by having an internal strategy within the organization, one of the which is the use of technology and digitization in the area of digital procurement and supply chain innovation.The research in based on survey with the distribution of questionnaire with of 25 questions that show the impact on digital procurement, supply chain innovation, supply chain performance and organization performance. From the result of this study can be conclude that digital procurement capabilities do not have a positive impact on supply chain performance, while supply chain innovation has a positive effect on supply chain performance. And supply chain performance has a positive effect on organizational performance.